Budget impact analysis of dabigatran compared with rivaroxaban in the prevention of the thromboembolic risk in patients with non-valvular atrial fibrillation - Celeste, Maria Grazia; De Marco, Francesca; Fresco, Claudio; Musumeci, Giuseppe; Ravasio, Roberto (Farmeconomia. Health Economics and Therapeutic Pathways, 2017)
BACKGROUND: Dabigatran 150 mg BID (D150) and rivaroxaban 20 mg (R20) are indicated for the prevention of thromboembolic events in patients with Non-Valvular Atrial Fibrillation (NVAF). Outcomes from observational study demonstrated that D150 and R20 reduced the rate of thromboembolic events.OBJECTIVE: This analysis estimated the budget impact of the use of D150 and R20 for the treatment of NAFV patients in Italy.METHODS: A budget-impact model (BIM) was developed to estimate the direct costs up to 12 months from an Italian NHS perspective. The resource utilization (drugs and intracranial hemorrhage or major extracranial bleeding event) was derived from an observational study. Only direct medical costs were considered. Ex-factory prices and National Tariffs were considered to estimate the costs of drugs and medical resource used, respectively. The BIM showed the difference of expenditure and clinical events (intracranial hemorrhage or major extracranial bleeding) generated by the base case calculated for current prescription volumes (D150 30%, R20 100%), and for different prescription volume scenarios (D150 at 70% and 100%). Key variables were tested in the sensitivity analysis.RESULTS: D150 was associated with a medical cost offset driven by fewer intracranial hemorrhage and major extracranial bleeding event, these offset the incremental drug cost and results in an annual saving per patient treated (D150: € 1,052.78; R20: € 1,161.23). The present scenario determines an annual cost of € 262,543,583. The impact of total annual costs for the Italian NHS would be lower if D150 prescription volumes would be higher. The total cost is predicted to decrease by 3.8% if the D150 prescription increase to 70% and it is predicted to decrease by 6.7% if the D150 prescription increase to 100%.CONCLUSION: The use of D150, as an alternative to R20 to prevent events in patients with NVAF, could represent a cost-saving option for the Italian NHS.